Legal review of airport pass service at the airport authority office in region ii medan when entering the security restricted area - Silvianda Silvianda; Ivan Manahan Sihombing; Zetria Erma (LEGAL BRIEF, 2023)
Airport Pass is an entry permit sign for individuals, vehicles, cargo and posts that will enter the Security Restricted Area, the requirements for obtaining which have been regulated in regulations issued by the Government. The purpose of this research is to conduct a legal review of the Airport Pass service at the Airport Authority Office in Region II Medan when entering the Security Restricted Area. The type of research in this paper is normative with a statutory and conceptual approach. While the specification of the research is analytical descriptive, namely explaining the problem according to the research title. The data used is secondary data which consists of primary legal materials in the form of Law No. 25 of 2009, Law No. 1 of 2009, Permenhub No. PM 33 TAHUN 2015, Permenhub No.PM 167 Year 2015, Permenhub No. PM 178 of 2015 and secondary legal materials in the form of books, journals, electronic news, and opinions of legal experts, laws and regulations, and writings related to research titles. Legal review of Airport Pass services at the Airport Authority Office in Region II Medan as a public service provider. Therefore, it is suggested to all partners or certain parties who already have an Airport Pass to always use it when entering the airport location and follow the usage regulations that have been set according to the mandate of the law regarding public services. Administrative sanctions for those who violate it for the sake of creating security and order in carrying out services in the Airport Region II Medan area.